Evaluation of Urinary Biomarkers for Early Detection of Upper Tract Urothelial Carcinoma: A Prospective Study - Zeeshan Shaukat, Ali Saqlain Haider, Muhammad Haroon Ghous, Muhammad Nadeem Shafique, Muhammad Adnan Sadiq, Nadeem Abbas (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Upper tract urothelial carcinoma (UTUC) is often diagnosed at advanced stages due to limitationsof imaging and cytology. The present prospective study investigated the diagnostic performanceof selected urinary biomarkers in detecting early-stage UTUC. The primary objective was toevaluate sensitivity, specificity